MODERN SPORT AND TOURISM AS TWO MUTUAL SUPPORTIVE AND COMPLEMENTARY FIELDS - Vukan Vujović; Peko Vujović; Marijana Tišma (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The development of the relationship between sport and tourism started yet in Ancient Greece and are continuing through the various forms and types in a sub¬sequent epochs and last to these days. The twentieth century was a period of unpre¬cedented general socio-economic development, and thus the development of sport and tourism. Democratization, the rise of social standards, and social modernization have led to an increasing number of members of the world community which has the oppor¬tu¬nity to participate in a various sports-recreational activities. Sport increasingly more represents a distinctive and very important social segment of the activities connected with the rest and relaxation. The interdependence of sport and tourism has not been yet fully elucidated. Sports tourism, in practice, has become extremely important and re¬pre¬sents a particular segment of tourism and tourist offer. The aim of this paper is to consider and point out to some aspects of their mutual dependence and conditionality, by analysis of the impact of some dominant sports on development and modernization of tourism resources, through customizing of the offered tourism facilities to the better and more quality sports-recreational de¬sti¬nation, and to the impact and importance of tourism resources in the affirmation of some new sports disciplines. Task of the paper is to show the complexity of the sports tourism impact on the wider community, in the form of development as an economic sector, factor of impro¬ve¬ment and enrichment of the site offering, with undeniable impact on the increase of the general cultural level of the population and increasing of life quality under the slogan: "training is a health."